Veillonella dispar and V. atypica increased the growth of Listeria monocytogenes in liquid culture and biofilm conditions - Fanie Shedleur-Bourguignon; William P. Thériault; Frédéric Berthiaume; Ibtissem Doghri; Jessie Longpré; Alexandre Thibodeau; Philippe Fravalo (PLoS ONE, 2025)
Listeria monocytogenes ( L. monocytogenes ) is a foodborne pathogen that causes severe illness in high-risk groups who face a mortality rate of 15% to 20% with exposure to this deadly bacterium. L. monocytogenes poses a significant food safety concern due to its ability to withstand the adverse conditions encountered in food production environments. Prevention of its entry into the ready-to-eat (RTE) processing environment is crucial, and consequently, preventing its establishment within the environmental microbiota of slaughterhouses—the preceding stage in the production chain—is essential. This can be a challenge because L. monocytogenes has the ability to create and persist in biofilms in association with microorganisms. The role of the accompanying microbiota in the survival and density of L. monocytogenes has been shown to range from having antagonistic to synergetic effects. The aim of the present study was to validate a positive association previously identified using bioinformatic tools between the presence of Veillonella spp. on conveyor belt surfaces of the cutting room of a swine slaughterhouse and the relative abundance of L. monocytogenes . Veillonella dispar ( V. dispar ) and Veillonella atypica ( V. atypica ) showed statistically significant positive effects on the growth and survival of the pathogen in both planktonic cultures and in biofilms tested under static and dynamic conditions. These effects of Veillonella appear to be mediated through compounds secreted or made available by the bacterium since contact with the supernatants of Veillonella cultures was sufficient to induce L. monocytogenes growth enhancement. This increase is primarily due to the live cell mass, suggesting that Veillonella acts at the L. monocytogenes cell population level rather than on the biofilm matrix. We believe that our results represent a step toward a better L. monocytogenes food safety risk assessment and could contribute to the development of better strategies against this pathogen.